Exploring preferred math learning tools for pre-service teachers - Falentino, Charlos; Dakhi, Grecellia Mei Magdalena; Medika, Anggara Duta; Mutang, Evanita; Febryan, Mohamad Ezra; Nuryadin, Atin; Sulaeman, Nurul Fitriyah (Primatika : Jurnal Pendidikan Matematika, 2024)
Pre-service teachers play an important role in teaching and influencing future learners. One of the important skills that prospective teachers must have is mathematical ability, so information about pre-service teachers' learning tool preferences in understanding mathematical concepts is crucial. This study aims to identify pre-service teachers' learning tool preferences for understanding mathematical concepts. This study used mixed methods, quantitative and qualitative. Data collection was carried out by distributing questionnaires to 129 prospective teachers from mathematics and science education study programs, as well as elementary school teacher education at Mulawarman University. Quantitative questions used Likert scale-type questions, and qualitative used free-response questions to get an in-depth analysis. The results of this study showed a very weak correlation between learning aid preferences and the understanding of basic math concepts, but it increased considerably when linked to advanced math concepts. In addition, there is a difference in preference between male and female pre-service teachers, where males are more likely to favor tools such as AI or ChatGPT, while females prefer learning videos. This study is expected to provide valuable information for policymakers to provide facilities that support the learning needs of pre-service teachers.